Caudal Anesthesia for Pediatric Subumbilical Surgery, Less Load on the Postoperative Recovery Unit - ABDULLAYEV, RUSLAN (CUREUS INC, 2019)
Introduction Caudal epidural anesthesia, when used as a sole method for surgical anesthesia, has favorable effects on the recovery duration and the time spent in the recovery unit. In this study we made a retrospective analysis of pediatric surgery operations under local, regional and general anesthesia. We aimed to find shorter postoperative recovery times with local and regional anesthesia. Materials and method Data of the pediatric patients undergone subumbilical surgery during the two-year period in Pediatric Surgery clinic were collected. The patients' age, sex, surgery type, anesthesia and airway control routes, as well as duration of anesthesia, operation and recovery were obtained. Results Data of 937 patients were analyzed, of whom 811 (86.6%) were males. Caudal anesthesia was performed in 240 patients (25.6%) and the mean age of these patients was 3.83 +/- 3.00 years. The patients with caudal and local anesthesia spent significantly less time in the postoperative recovery unit, compared with general anesthesia groups (P < 0.001). Conclusion Caudal anesthesia as a sole method for pediatric subumbilical surgery is a relatively safe method. Patients having operation under caudal anesthesia have faster discharge times from postoperative recovery units, compared with general anesthesia. This probably reduces recovery unit expenditures.
Keywords: caudal anesthesia; caudal block; pediatric anesthesia; general anesthesia; local anesthesia; recovery unit; NERVE BLOCK; REGIONAL ANESTHESIA; URINARY RETENTION; EPIDURAL BLOCK; PENILE BLOCK; CHILDREN; INFANTS; PAIN; BUPIVACAINE; ULTRASOUND